Telemedicine-based adapted physical activity programs for pediatric oncology patients in active oncological care: a feasibility study - Peli, Linda; Inselvini, Elisa; Cogliati, Marta; Finazzi, Eleonora; Gorio, Chiara; Angeloni, Alessia; Pollet, Joel; Schumacher, Richard F.; Porta, Fulvio; Bertoni, Filippo; Gobbo, Massimiliano (Frontiers in Oncology, 2025)
BackgroundSurvival rates for pediatric hematological malignancies have significantly improved over the last 50 years. However, children undergoing cancer treatment face long- term health challenges, including musculoskeletal impairments and reduced physical activity levels, which contribute to poorer quality of life (QoL) and elevated cardiovascular risks. Barriers to accessing traditional physical activity and rehabilitation programs necessitate innovative approaches like telemedicine-based interventions.ObjectiveThe primary objective was to evaluate the feasibility and adherence of a telemedicine-integrated adapted physical activity (APA) program in pediatric oncology patients. Effectiveness, in terms of functional and psychosocial outcomes, was considered as an exploratory secondary endpoint. Although some statistically significant findings were observed, these results should be interpreted as supportive evidence and not as definitive proof of effectiveness.MethodsThe study included children and adolescents (5–18 years) with onco-hematological conditions. Participants underwent baseline (Pre-APA) and six-month (post-APA) assessments using different functional tests and validated QoL evaluation tools (PedsQLTM). The intervention comprised personalized exercise regimens targeting strength, aerobic capacity, flexibility, and balance. Supervised training sessions were conducted both in-person and remotely via telemedicine solutions. Secondary outcomes included quadriceps muscle and hand- grip strength, balance, fatigue, and health-related QoL. Statistical analyses utilized mixed regression models to evaluate pre-post intervention changes and the impact of remote training.ResultsEighteen subjects (8 female, median age 12 years) were included. The APA program demonstrated high adherence (median 77.08%). Preliminary improvements were observed in QoL (PedsQLTM child, p=0.007), fatigue (p=0.035), and functional performance (chair stand test, p=0.033). Regression analysis indicated a positive correlation between remote training frequency and QoL improvement (p=0.027, R²=0.235). Although strength measures showed no significant improvement, remote training influenced flexibility outcomes. Parental perceptions of fatigue and QoL also improved (p=0.049).ConclusionTelemedicine-based APA programs are a feasible and effective approach for enhancing QoL and functional capacity in pediatric oncology patients. These preliminary findings support the integration of digital health solutions in long-term survivorship care, though larger studies are needed to confirm these results.